2014
DOI: 10.1597/14-212r
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Amblyopia and Its Risk Factors in Children With Isolated Metopic Craniosynostosis

Abstract: In our patient population, children with isolated metopic craniosynostosis demonstrate an increased rate of amblyopia and its risk factors. Amblyopia is best treated early in life to achieve a successful outcome. A referral to a pediatric ophthalmologist for a formal eye exam and potential treatment is therefore recommended for children with isolated metopic craniosynostosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…No child with metopic craniosynostosis in our group had strabismus preoperatively, but one patient developed strabismus postoperatively. This is in agreement with other studies, where low prevalence rates of strabismus in metopic craniosynostosis are seen 10 16 21. There are reports on iatrogenic induction of strabismus from the fronto-orbital surgery itself 22 23.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…No child with metopic craniosynostosis in our group had strabismus preoperatively, but one patient developed strabismus postoperatively. This is in agreement with other studies, where low prevalence rates of strabismus in metopic craniosynostosis are seen 10 16 21. There are reports on iatrogenic induction of strabismus from the fronto-orbital surgery itself 22 23.…”
Section: Discussionsupporting
confidence: 92%
“…Most studies describe the outcome in metopic and unicoronal craniosynostosis. [10][11][12][13][14][15] Vasco et al 5 followed 29 children, including all subtypes, up to 1 year after surgery and concluded that abnormalities of visual function were more frequent preoperatively and that there was an improvement after surgery, though implying that it could be a sign of delayed visual maturation. Chieffo et al 16 recently reported on a large cohort of 142 children with non-syndromic craniosynostosis and found high rates of neuro-ophthalmological or neuro-visual deficits at the time of diagnosis, improving 1 year after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Given the risk for amblyopia and the need for treatment early in life, referral to a pediatric ophthalmologist for a formal eye exam and potential treatment is recommended for patients with isolated nonsyndromic CS. 15 The purpose of this study was to describe preoperative and postoperative ophthalmic EICP markers and ophthalmic findings in nonsyndromic CS patients to provide an overview of the early ophthalmology needs in a clinical population.…”
mentioning
confidence: 99%